Shariah Governance Practice on Indonesian Islamic Banks - Muhfiatun; Prasojo, Prasojo; Listiyorini, Inon; Utami, Ristianawati Dwi (Journal of Business Management and Islamic Banking, 2024)
Research Aims: This study aims to assess the implementation of Shariah governance in Indonesian Islamic banks. Methodology: This study utilises a qualitative approach coupled with content analysis; this study evaluates the alignment of Sharia Supervisory Board (SSB) practices with relevant regulations. Research Findings: The analysis revealed that none of the Islamic banks breached regulations or deviated from the prescribed criteria in the Sharia Supervisory Board (SSB) recruitment or characteristics. Theoretical Contribution: This study is poised to enrich the diversity of backgrounds within the Sharia Supervisory Board (SSB), aiming to elevate its overall quality. Research limitation and implication: This study exclusively examines the framework of Sharia governance within the context of Indonesia, and therefore, the findings should be separate from diverse country contexts.